Teaching contributions from secondary school subject areas to education for sustainable development - a comparative study of science, social science and language teachers - Sund, Per; Gericke, Niklas (Environmental education research, 2020)
In many countries' policy documents and curricula, teachers in the subject areas of science, social science and language are encouraged to collaborate on cross-curricular issues such as sustainable development (SD). This study is conducted in secondary schools (compulsory years 7-9) in Sweden and investigates the similarities and differences in the responses of ten teacher groups (forty-three teachers in total) to questions about their teaching contributions in their own subject areas to education for sustainable development (ESD). The overall aim is to understand how teachers of these three subject areas can contribute to cross-curricular teaching in teacher teams in the context of ESD. This is done by analysing the group responses from data collected in group discussions concerning the teaching dimensions what (content), how (methods) and why (purposes) in relation to ESD. We first analyse the teacher group responses and arguments regarding their contribution to ESD teaching from each subject area separately. Thereafter, we comparatively analyse how the different subject areas' contributions overlap or complement each other in a potential collaborative ESD teaching. The results show that teachers from different subject areas stress different yet complimentary dimensions of teaching and perspectives of ESD. The implications for cross-curricular teaching in ESD are also discussed.